Bilateral Pars Defects at the L4 Vertebra Result in Increased Degeneration When Compared With Those at L5: An Anatomic Study - McCunniff, Peter T. (Clin Orthop Relat Res, 2015)
BACKGROUND: Cadaveric studies have examined disc degeneration at the L4-L5 and L5-S1 motion segments; however, we are not aware of another study that has examined the relationship between bilateral spondylolysis and its effect on degenerative disc disease at those levels. This may have been overlooked by researchers owing to the majority of spondylolysis occurring at the L5 vertebra. QUESTIONS/PURPOSES: Using osteologic specimens from a collection that included individuals who died in one city in the USA between 1893 and 1938, we asked: (1) do specimens with bilateral spondylolysis (bilateral pars defects) have increased levels of disc degeneration, at their respective motion segments, when compared with matched controls without spondylolysis, and (2) is the finding of a bilateral pars defect associated with more severe arthritis at L4-L5 than at L5-S1? METHODS: An observational study was performed on 665 skeletal lumbar spines from the Hamann-Todd Osteologic Collection at the Cleveland Museum of Natural History (Cleveland, OH, USA). The specimens included 534 males and 131 females ranging from 17 to 87 years old, with a nearly bell-shaped distribution of ages for males and a larger proportion of younger ages in the female specimens. Of those with spondylolysis, 81 had a defect at L5 and 14 had a defect at L4. The gross specimens were examined subjectively for evidence of arthrosis. At the time of examination, specific attention was not paid to the coexisting presence or absence of spondylolysis nor was the examiner blinded to the age of the specimens. Disc degeneration was measured by the classification of Eubanks et al., a modified version of the Kettler and Wilke classification. Linear regression was performed to derive a formula that would predict the amount of disc degeneration at L4-L5 and L5-S1 for the normal control population given a specimen’s age, sex, and race. We then used this formula to evaluate the difference in disc degeneration at the corresponding level of the pars defect that is greater than the predicted amount for a control without spondylolysis. This allowed us to conclude that any significant differences found between the L4-L5 and L5-S1 cohorts were attributable to factors not simply inherent to their functional position in the spine of an individual without a bilateral pars defect. RESULTS: L4 spondylolysis and L5 spondylolysis showed greater amounts of degeneration compared with that of matched controls (L4 controls: mean = 1.52, SD = 0.74; L4 spondylolysis: mean = 3.21, SD = 0.87; p < 0.001; L5 controls: mean = 0.97, SD = 0.48; L5 spondylolysis: mean = 2.06, SD = 0.98; p < 0.001). When we controlled for the expected amount of degenerative disc disease at each level in controls, the observed degeneration was more severe at L4-L5 than at L5-S1 (p = 0.008, R-squared = 18.6). CONCLUSIONS: L4-L5 and L5-S1 bilateral spondylolysis groups had increased presence of degenerative disc disease compared with those without bilateral spondylolysis. For the same degree of spondylolysis, the observed amount of disc degeneration was greater at the L4-5 motion segment compared with L5-S1. CLINICAL RELEVANCE: Although not as common as the spondylolysis at L5-S1, we believe that our findings support that patients with L4-L5 spondylolysis can expect a greater degree of degenerative disc disease and increasing clinical symptoms. Multiple factors in the sacropelvic geometry of an individual, facet morphologic features at L4-L5, and the absence of the iliolumbar ligament at this level are possible contributing factors to the findings of this study.